Automation of water tank management system for residential Areas. (2022) - Kalamani, M.; Sakthi Sri, S.B.; Sugan, G.G.; Edward Bensteve, S.R.; Rajkumar, P.
Abstract: Water resource management is the practice of planning, producing, distributing, and managing the water resources. Water cycle needs to be managed efficiently to utilize the resource completely without wasting it. Over the past few decades, the concept of automation plays a major role in the industry and homes for the development of futuristic ideas. The feasibility of existing and upcoming water resource distribution is one of the most pressing challenges for the water related sources in the future. As water becomes scarce and costly, water management becomes increasingly important and finding a balance between human requirements and the critical step of environmental water resource sustainability. Some of the home appliances have been automated and exist in many places. Even though it has been automated, most of the systems work in wired system environments. Wireless systems attracted the attention of researchers to find out the way for monitoring the water level by using the system. In this research work, a mobile controlled water tank management system is proposed for taking the technology to the next level as a wireless one. This product is suitable for both individual villas and high storey apartments. This model reduces the amount of product and helps to control excessive power consumption. It helps us to monitor the usage of water per person or water consumption per home.